2012
DOI: 10.1111/myc.12024
|View full text |Cite
|
Sign up to set email alerts
|

Candiduria in haematologic malignancy patients without a urinary catheter: nothing more than a frailty marker?

Abstract: Summary Background There is scarcity of data regarding significance of candiduria in patients with hematologic malignancies and its association with invasive candidiasis. Patients and Methods To that end, we retrospectively evaluated all hospitalized, non-intensive care unit patients with hematologic malignancies and candiduria during a 10-year period (2001-2011). To decrease the possibility of bladder colonization and sample contamination, we excluded all patients with candiduria who had urinary catheters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…We observed a high mortality rate (15%); this is likely a marker for severity of illness, rather than the consequence of candiduria itself, as suggested by previous studies in general population: Kauffman et al observed an overall mortality of 19.8%, but candiduria‐related mortality was only 0.4%. In our study, treatment had no significant effect on complications nor on survival rate.…”
Section: Discussionsupporting
confidence: 80%
“…We observed a high mortality rate (15%); this is likely a marker for severity of illness, rather than the consequence of candiduria itself, as suggested by previous studies in general population: Kauffman et al observed an overall mortality of 19.8%, but candiduria‐related mortality was only 0.4%. In our study, treatment had no significant effect on complications nor on survival rate.…”
Section: Discussionsupporting
confidence: 80%
“…Although C. albicans is reported as the major Candida species causing candiduria in some studies [ 3 , 16 , 19 , 20 ], an increasing trend in the prevalence of candiduria due to non- albicans Candida species was shown by some researchers [ 2 , 21 - 23 ]. In the present study, C. glabrata was the most isolated species (50%) followed by C. albicans (31.6%), C. krusei (10.5%), C. tropicalis (5.3%), and C. kefyr (2.6%).…”
Section: Discussionmentioning
confidence: 99%
“…According to the data from a study conducted by Georgiadou et al [ 23 ], female gender, multiple hospitalization, broad-spectrum antimicrobial the-rapy, renal dysfunction, intensive care unit admission, and diabetes mellitus are predisposing factors of candiduria in patients with hematologic malignancy. In addition to urinary system disorders following candiduria, candidemia is reported to be significantly associated with the candiduria [ 26 ], which underscores the importance of this condition.…”
Section: Discussionmentioning
confidence: 99%
“…Many physicians who care for neutropenic patients treat those who have fever and candiduria because the candiduria may indicate invasive candidiasis. However, a recent study from a cancer hospital of a small number of patients, 25% of whom were neutropenic, found that these patients did not develop candidemia or other complications of candiduria [484]. Several reports have documented a high rate of candidemia when patients undergo urinary tract instrumentation [485,486], which has led to recommendations to treat with antifungal agents periprocedure.…”
Section: Evidence Summarymentioning
confidence: 99%